(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
The purpose of this study is to determine the effect of Current Ratio, Debt to Equity Ratio, Return On Asset, dan Earnings Per Share both simultaneously and partially on stock prices. The total of population in this study were 15 companies and the research sample was 13 financing service companies registered on the IDX, taken using criteria determined by the author. The analytical method used is multiple linear regression.